Análisis y Diseño de un sistema web de facturación electrónica utilizando los servicios de Rentas Internas para la Empresa System Labs de la ciudad de Loja - Riofrío Terrazas, Francisco Geovanny (2025)
The following Title Project, (TT for its acronym), deals with the development of the analysis and design of a web system for electronic invoicing, taking as a case study, the company System Labs of the city of Loja. The objective of the TT, in its preliminary phase, is the analysis and design, defining the artifacts, such as functional and non-functional requirements, glossary of terms, domain model, use cases, with their respective description. In the design, the final class diagrams, robustness, sequence, the type of architecture and the design pattern are made. To develop the analysis and design phases, the ICONIX methodology was selected. In the analysis phase, do it following the IEEE 830 standard for software requirements specification, where you make a document to describe and present the functional and non-functional requirements. In the Design phase, I used UML modeling, the same one that allowed me to make the diagrams and define a type of architecture and design pattern. The results obtained from this TT are the technological tools investigated to be implemented in the analysis and design phase, functional and non-functional requirements, glossary of terms, domain model, use cases with their respective diagram and description, the diagram of final classes, robustness diagrams, sequence, monolithic architecture and the Model View Controller (MVC) design. As a conclusion of the TT, the usefulness of the tools used in the different phases of the TT was determined, such as ICONIX that helped me to carry out an established order on the software development phase, the IEEE 830 standard, allowed me to carry out a good analysis of requirements since it documents the requirements in an orderly manner, UML, the same one that was used for the creation of the diagrams, in order to have a clearer vision of the software life cycle.